DZIP1 Promotes Proliferation, Migration, and Invasion of Oral Squamous Carcinoma Through the GLI1/3 Pathway - Wangxiang Yan; Yun Deng; Yuhang Zhang; Jing Luo; Dunlang Lu; Quan Wan; Lijuan Mao; Yu chen (Translational Oncology, 2019)
BACKGROUND: DZIP1 is an oncogene involved in the progression and stemness of carcinoma through the Wnt/β-catenin pathway, and the potential mechanism of DZIP1 in oral squamous cancer remains unknown. The aim of this study was to uncover the effect and mechanism of DZIP1 in the progression of oral squamous carcinoma. METHODS: TCGA database scanning was applied to verify dysregulated genes in oral squamous carcinoma. quantitative real-time polymerase chain reaction, immunohistochemistry, and Western blotting assays were used to detect the expression of DZIP1 in tissues and cell lines. We established stable DZIP1-overexpressing and DZIP1 knockdown cell lines. We investigated the biological function and the underlying mechanism of DZIP1 through a series of experiments. RESULTS: DZIP1 was one of the genes discovered by the scanning strategy to be upregulated in cancer tissue and negatively correlated with the overall survival (OS) of patients. DZIP1 promotes proliferation, migration, and invasion in an oral squamous carcinoma cell line through EMT in a GLI1/3-dependent manner. CONCLUSIONS: DZIP1 promotes the proliferation, migration, and invasion of oral squamous carcinoma through the GLI1/3 pathway.